Environment Uncertainty, Earnings Volatility and Their Role in Financial Statement Fraud? - Lin Oktris; Agustin Fadjarenie; Apollo Daito; Zuha Rosufila Bt Abu Hasan (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study examines the influence of environmental uncertainty (EU) and earnings volatility (EV) on fraudulent financial statements (FFS) in Indonesia’s manufacturing sector. The research utilises observational data from 902 instances across 188 manufacturing companies from 2019 to 2023, employing multiple regression analysis to test the relationships between variables. The results reveal that EV has a significant positive effect on FFS, while EU does not show a significant impact. The novelty of this study lies in its integrative approach, considering the interactive effects between EU and EV, which have been underexplored in previous literature. The findings suggest that high earnings volatility can be an early indicator of financial statement manipulation. The practical implications emphasise the importance of closely monitoring earnings volatility by regulators and auditors as a preventive measure against financial fraud and strengthening internal control mechanisms and corporate governance to minimise the risk of financial statement manipulation.